Innovation in solid heterogeneous catalysis for the generation of economically viable and ecofriendly biodiesel: A review. Issue 2 (2nd April 2016) - Avhad, M. R.; Marchetti, J. M.
ABSTRACT: Among the possible options for the transformation of plant oils and animal fats to biodiesel, the alcoholysis process has been frequently selected. The rate of alcoholysis reaction is accelerated using a catalytic material. This article reviews different nature of catalysts utilized to assist the process of biodiesel production. The chemical properties of both homogeneous and heterogeneous catalysts enable their sub-division into acidic and basic materials. The proficiency of several heterogeneous catalytic systems and the possible route of alcoholysis reaction using different materials is systematically discussed. Furthermore, the factors influencing the performance of catalysts are also considered.